Vespers Rising: The 39 Clues #11 - Riordan, Rick (New York : Scholastic Inc., 2011)
Amy Cahill and her younger brother Dan thought they could return to their regular lives, but the Vespers, powerful enemies, will stop at nothing to get the clues that safeguard their family's great power.
Keywords: Brothers and sisters -- Fiction; Orphans -- Fiction; Family secrets -- Fiction; Adventure and adventurers -- Fiction; Siblings -- Fiction; Orphans -- Fiction; Secrecy -- Fiction; Adventure fiction